Pengaruh CAR, NIM, BOPO, dan LDR terhadap Tingkat Profitabilitas (pada bank umum go public periode 2008-2012 - Muhammad Aldi; Hari Susanta Nugraha; Saryadi Saryadi (Universitas Diponegoro, 2015)
Bank is the industries which the main activity of the bank itself is fund gathering from public to obtain earnings. The ratio that used for the profitability is ROA and ROE, because it can identify the ability of bank management in managing the assets under their control to generate the income. To see the performance of a bank compared to the other banks, we can compare the absolut figures and financial ratios that achieved from the bank. Because of that thing that already explained, this study named CAR, NIM, BOPO, dan LDR as a ratio that are considered to affect the profitability of the bank. This study aims to determine the effect of the CAR, NIM, BOPO,and LDR against the Profitability level during the period 2008-2012 . Methods in this research using secondary data of each variable . The sample in this study amounted to 35 go public banks period 2008-2012 with purposive sampling technique. Scale measurements using a measuring scale ratio. In linear regression analysis was used and the significance test using SPSS 15.0 .From the results of the data analysis it can be concluded that , CAR has a significant effect on profitability. NIM has a significant effect on profitability. BOPO has a significant effect on profitability. LDR has no effect on profitability. Simultaneously, CAR, NIM, BOPO, and LDR has a significant impact on profitability amounted to 95,6 % . NIM has the biggest impact with 0,350 standardized coefficient beta score. The researchers suggest that management also consider the other factors beside CAR, NIM, BOPO, dan LDR for consideration in analysing the level of bank profitability.